Incentive diversity is key to the more effective and equitable governance of marine protected areas - Jones, Peter J. S.; Stafford, Richard; Hesse, Isabel; Khuu, Duong T. (Frontiers in Marine Science, 2024)
A target to conserve 30% of oceans by designating marine protected areas (MPAs) has been agreed, yet the effectiveness of existing MPAs is often low, with few weakly implemented restrictions on impacting uses. Drawing on coevolutionary governance and social-ecological systems concepts, we hypothesize that (1) effective governance frameworks for MPAs rely on various combinations of diverse incentives, which encourage people (actors) to behave in a manner that reduces the impacts of their uses and thereby more effectively achieves conservation objectives; (2) effective MPAs will tend to employ a higher diversity of governance incentives, creating resilient MPAs analogous to resilient ecosystems with higher species diversity. This multiple case study empirical analysis of the governance of 50 MPAs supports these hypotheses and demonstrates that: (a) there is strong correlation between the effectiveness of MPAs and the number of governance incentives used; (b) combinations of economic, legal, communication, knowledge and participatory incentives are shown to be employed in effective MPAs and mostly needed in less effective MPAs; (c) whilst some incentives are frequently identified as being important to promote effectiveness, no particular ‘magic wand’ incentive or ‘best practice’ combinations of incentives guarantee this. These findings show that effectiveness is not determined by any specific governance approaches or incentives, but rather the combination of a diversity of functionally integrated incentives, which interact with and support one another to promote MPA effectiveness and resilience, i.e. diversity is the key to resilience, both of species in ecosystems and incentives in governance systems.